2009
DOI: 10.1111/j.1439-0426.2008.01075.x
|View full text |Cite
|
Sign up to set email alerts
|

Age, growth and feeding of the common stingray (Dasyatis pastinaca, L., 1758) in the Cilician coastal basin, northeastern Mediterranean Sea

Abstract: Growth and feeding of stingray (Dasyatis pastinaca) were studied using 346 specimens from the Cilician Basin coastal area (northeastern Mediterranean). Age classes between 0 to XII were found. The total length of all specimens ranged from 14.6 to 100.9 cm, and total weight was between 22.5 and 6800 g. Total length (TL)-weight (W) and disc width (DW)-weight (W) relationships were W = 0.0033*L 3.1429 and W = 0.0039*DW 3.4914 , respectively. The age data, derived from central readings, were used to estimate the v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
34
1
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 8 publications
4
34
1
3
Order By: Relevance
“…A previous study that used stable isotopic compositions of amino acids found a TEF of 3.6 ‰ more accurately represented penguin TPs (Lorrain et al 2009). That difference was attributed to the use of blood samples for isotopic analysis, whereas earlier studies had used whole animal or muscle tissue (McClelland & Montoya 2002, Chikaraishi et al 2007, 2009, Popp et al 2007, Hannides et al 2009).The use of muscle in the present study precludes tissue biochemical effects as a viable explanation for the lower observed TEF from amino acid analysis. Alternatively, lower observed TEFs in brown stingray and juvenile scalloped hammerhead shark muscle may be due to lower reaction rates involving glutamic acid as a consequence of urea retention for osmotic regulation (Evans et al 2004).…”
mentioning
confidence: 71%
See 4 more Smart Citations
“…A previous study that used stable isotopic compositions of amino acids found a TEF of 3.6 ‰ more accurately represented penguin TPs (Lorrain et al 2009). That difference was attributed to the use of blood samples for isotopic analysis, whereas earlier studies had used whole animal or muscle tissue (McClelland & Montoya 2002, Chikaraishi et al 2007, 2009, Popp et al 2007, Hannides et al 2009).The use of muscle in the present study precludes tissue biochemical effects as a viable explanation for the lower observed TEF from amino acid analysis. Alternatively, lower observed TEFs in brown stingray and juvenile scalloped hammerhead shark muscle may be due to lower reaction rates involving glutamic acid as a consequence of urea retention for osmotic regulation (Evans et al 2004).…”
mentioning
confidence: 71%
“…Alpheids are a common prey item for dasyatids from Florida and the eastern Mediterranean Sea (Snelson & Williams 1981, Yeldan et al 2009), whereas portunids were common in the diets of dasyatids from the central Bahamas and the western Atlantic Ocean (Struhsaker 1969, Gilliam & Sullivan 1993. Site-specific differences in prey abundances probably contribute to a lower importance of crustaceans for some dasyatid rays.…”
Section: Foraging Ecologymentioning
confidence: 99%
See 3 more Smart Citations